Pengaruh Zat Pengatur Tumbuh Alami Terhadap Jumlah Akar dan Jumlah Daun Planlet Anggrek Bulan (Phalaenopsis amabilis) Secara In Vitro : Effects of Natural Growth Regulators on Number of Roots and Leaves in Planlets of Phalaenopsis amabilis (Moth Orchid) In Vitro - Nova Triani; Achmad Ilham (Gontor Agrotech Science Journal, 2024)
The moth orchid (Phalaenopsis amabilis) is a popular ornamental plant due to its beautiful flowers. Propagation of moth orchids can be performed using tissue culture or in vitro methods. The medium used in moth orchid tissue culture is the MS (Murashige and Skoog) medium, which is enriched with plant growth regulators (PGRs). The use of natural PGRs, such as onion extract and coconut water, can serve as an alternative and potential source nutrition substitute for synthetic PGRs in orchid tissue culture media. This study aims to determine the effect of using natural PGRs, namely onion extract and coconut water, on moth orchid plantlets. The method employed is a Complete Randomized Design (CRD) factorial experiment with two factors: the first factor is the concentration of onion extract (0 g/L, 20 g/L, 30 g/L, and 40 g/L), and the second factor is the concentration of coconut water (0 mL/L, 50 mL/L, 100 mL/L, and 150 mL/L). Observations were focused on the increase in the number of roots and leaves. The results showed that a concentration of 20 g/L onion extract had a significant effect on the increase in the number of roots but did not affect the increase in the number of leaves. Meanwhile, the concentration of coconut water did not affect the increase in the number of roots or leaves.